Effect of binder-aggregate ratio and glass powder on the performance of concrete cured in different media - Temitope Awolusi; Marc Azab; Oussama Accouche; Precious Ajayi; Emeka Nnochiri (AIMS Materials Science)
The current approach to producing concrete is believed to be unsustainable because of its significant consumption of cement and aggregate, thereby causing environmental risks and improper curing of concrete, which could lead to lower durability and increased permeability. This study investigated the use of glass powder as a partial replacement for cement by testing the output concrete with three different curing methods. The percentage replacement of glass powder in cement varied from 0%, 10%, and 20% for varying binder/aggregate ratios of 0.35, 0.46, and 0.57, respectively. Results show that the concrete mix with a binder/aggregate ratio of 0.46 had the highest slump value. The samples cured in liquid coatings of lime solution had the highest mean density of 2575 kg/m3, which makes lime curing the most appropriate method if permeability is a desired concrete property. Water curing produced the highest compressive strength of 17.27 N/mm2 at an optimum binder/aggregate ratio of 0.46. The findings show that increasing the aggregate content of concrete mix with subsequent wet curing will most likely decrease concrete permeability. The use of waste glass as a partial replacement for cement is recommended as it improves the structural performance of concrete.